152 Recurrent Cytogenetic Abnormalities in Intravascular Large B-Cell Lymphoma. (11th January 2018) - Klairmont, Matthew; Cheng, Jinjun; Murray, Glenn; Gradowski, Joel
Abstract: Introduction: Intravascular large B-cell lymphoma (ILBCL) is a rare (<1 per 1, 000, 000) and aggressive extranodal lymphoma characterized by the proliferation of lymphoma cells almost exclusively within the lumina of small and intermediate vessels. While ILBCL has been associated with complex karyotypes, data characterizing its cytogenetic landscape and the presence of recurrent cytogenetic abnormalities are limited. Here, we present the results of the largest pooled dataset to date. Methods: An institutional database was queried for cases of ILBCL with complete cytogenetic analysis and a literature search was performed using PubMed to identify all published cases of definitively diagnosed ILBCL for which a complete karyotype was provided. The identified karyotypes were systematically reviewed for the presence of recurrent abnormalities. Results: Four new cases were identified and pooled, with 25 karyotypes previously published in the literature. Twenty of 29 (69%) patients had abnormalities involving chromosome 1. Ten translocations were present in eight patients, six of which involved either p13 or q21. In three additional patients, three rearrangements involving these breakpoints were also present. Thus, nine of 29 patients had rearrangements involving 1p13 or 1q21. 17/29(58.6%) patients had abnormalities involving chromosome 3. The most common rearrangement was a translocation, which was definitively present in eight patients, of which four (50%) involved 3p21. Seventeen of 29 (58.6%) patients had abnormalities involving chromosome 6. In almost all cases, the long arm of chromosome 6 was implicated, including seven patients with additional material of unknown origin and four 6q deletions. Twelve patients (41.4%) had abnormalities involving chromosome 14, nine (31% of total) of which involved rearrangements of 14q32. Sixteen patients (55.2%) had abnormalities of chromosome 18. Ten of 29 total patients (34.5%) had trisomy 18. Conclusion: ILBCL is associated with multiple recurrent cytogenetic abnormalities, the identification of which may facilitate diagnosis. Further research is warranted to determine the prognostic significance of these aberrations.